PURIFICATION AND PROPERTIES OF MANNANASE FROM Aspergillus ustus BL5 - Thontowi, Ahmad; Rahmani, Nanik; Andriani, Ade; Yopi, - (Teknologi Indonesia, 2014)
Strain of BL5 was reported as a mannanase producer. The purposes of this study are identification, purification and characterization of mannanase from BL5. The Internal Transcribed Spacer (ITS) regions analysis showed that BL5 strain have 93% similarity with Aspergillus ustus isolate UOA/HCPF 9236. An extracellular mannanase from the culture supernatant of a fungus A. ustus BL5 was purified. SDS-PAGE of the purified enzyme showed a single protein band of molecular mass 50 to 51 kDa. The mannanase exhibited optimum catalytic activity at pH 7.0 and 55C. The metal ions Ca2+, Cu2+ and SDS inhibited complete enzyme activity. The metal ion Mg2+ and EDTA increased complete enzyme activity. The value of Vmax = 5,88 ?mol mannose/min/ml and Kmax = 0.64 mg/ml. Mannanase of A. ustus BL5 be able to hydrolyzed porang mannan.